2021
DOI: 10.3389/fendo.2021.648411
|View full text |Cite
|
Sign up to set email alerts
|

Pasireotide in the Personalized Treatment of Acromegaly

Abstract: The delay in controlling the disease in patients who do not respond to first-line treatment with first generation somatostatin receptor ligands (first-generation SRLs) can be quantified in years, as every modification in the medical therapy requires some months to be fully evaluated. Considering this, acromegaly treatment should benefit from personalized medicine therapeutic approach by using biomarkers identifying drug response. Pasireotide has been positioned mostly as a compound to be used in first-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 91 publications
0
21
0
3
Order By: Relevance
“…Coopmans et al (24) showed that biochemical response to pasireotide-LAR is associated with high T2-signal intensity, whereas patients with a lower SST2 receptor expression have a greater chance to achieve tumor shrinkage. In general, good candidates for pasireotide treatment might be patients poorly responding to first-generation SRLs with high expression of SST5 receptor, with low AIP expression, those with SG tumors and with high Ki-67 index (49). The importance of clinical factors in terms of response to pasireotide-LAR has not been so widely discussed as molecular factors.…”
Section: Discussionmentioning
confidence: 99%
“…Coopmans et al (24) showed that biochemical response to pasireotide-LAR is associated with high T2-signal intensity, whereas patients with a lower SST2 receptor expression have a greater chance to achieve tumor shrinkage. In general, good candidates for pasireotide treatment might be patients poorly responding to first-generation SRLs with high expression of SST5 receptor, with low AIP expression, those with SG tumors and with high Ki-67 index (49). The importance of clinical factors in terms of response to pasireotide-LAR has not been so widely discussed as molecular factors.…”
Section: Discussionmentioning
confidence: 99%
“…sparsely granulated adenomas with low SSTR2 and E-cadherin expression, high SSTR5 expression, and low AIP and high Ki-67 expression, the recommended treatment of choice is PAS-LAR (Table 2 ). However, these recommendations should be verified in larger populations of patients with acromegaly [ 52 ]. Chiloiro et al evaluated the efficacy of PEGV and PAS-LAR in 74 patients resistant to first-generation SRLs therapy.…”
Section: Pasireotide In the Treatment Of Acromegalymentioning
confidence: 99%
“…Radiological, molecular and pathologic factors influencing response to the different SRLs in the medical treatment of acromegaly[50][51][52] …”
mentioning
confidence: 99%
“…При преимущественном воздействии на 5-й подтип соматостатиновых рецепторов он способен стабильно блокировать секреторную и пролиферативную активность опухолевых клеток, предотвращая дальнейшее развитие патологических изменений. Среди нежелательных явлений, возникающих при приеме продленной формы пасиреотида, следует отметить высокий риск нарушения углеводного обмена, что ограничивает его широкое применение [21].…”
Section: Problems Of Diagnosis and Treatment Of Acromegalyunclassified